2013
DOI: 10.1007/s10195-013-0266-7
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar variance as a predictor of persistent instability following Galeazzi fracture-dislocations

Abstract: BackgroundWe investigated the radiographic parameters that may predict distal radial ulnar joint (DRUJ) instability in surgically treated radial shaft fractures. In our clinical experience, there are no previously reported radiographic parameters that are universally predictive of DRUJ instability following radial shaft fracture.Materials and methodsFifty consecutive patients, ages 20–79 years, with unilateral radial shaft fractures and possible associated DRUJ injury were retrospectively identified over a 5-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Tsismenakis T and Tornetta P [ 11 ] on the contrary, reported that the radiographic parameters of >5 mm shortening and fractures within 7.5 cm of the joint are not reliable predictors of instability as their positive predictive values were 29% and 19% in respect; the presence of an ulnar styloid fracture may be more helpful (4/7 such cases had an instability). Takemoto R et al [ 12 ] reported that ulnar variance, rather than the absolute distance between the DRUJ and the fracture, is the most reliable predictor of post-fixation persistent DRUJ instability; for each 1 mm of variance away from neutral, there was a 26 % increase in the odds of having DRUJ instability with a 95% CI. In rare instances, the DRUJ joint remains irreducible after fixation of the radial shaft fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Tsismenakis T and Tornetta P [ 11 ] on the contrary, reported that the radiographic parameters of >5 mm shortening and fractures within 7.5 cm of the joint are not reliable predictors of instability as their positive predictive values were 29% and 19% in respect; the presence of an ulnar styloid fracture may be more helpful (4/7 such cases had an instability). Takemoto R et al [ 12 ] reported that ulnar variance, rather than the absolute distance between the DRUJ and the fracture, is the most reliable predictor of post-fixation persistent DRUJ instability; for each 1 mm of variance away from neutral, there was a 26 % increase in the odds of having DRUJ instability with a 95% CI. In rare instances, the DRUJ joint remains irreducible after fixation of the radial shaft fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple provocative maneuvers and preoperative radiographic parameters have been demonstrated to have high sensitivity for detecting DRUJ instability. [10][11][12][13][14][15][16][17][18][19] These include the RU stress test (also known as the piano key or shuck tests), ulno-carpal stress tests, and the ballottement test but are limited secondary to their subjective assessment of laxity 1,3,5 with low inter-rater reliability. 20 Moriya and colleagues examined the ability of these tests to detect the effect of TFCC tears on the DRUJ stability.…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, all patients deemed having DRUJ instability were immobilized for 6 weeks before initiating therapy. Patients were assessed as having persistent DRUJ instability if there was dorsal subluxation of the ulna on the lateral radiographs of the wrist, difference in laxity compared with the contralateral side as determined by the treating surgeon, magnetic resonance imaging evidence of a TFCC injury, or a dorsally prominent ulnar head in the setting of decreased supination (Takemoto et al., 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Several radiographic methods of diagnosis have been used to evaluate DRUJ instability in radial shaft fractures. These include radial shortening greater than 5 mm (Moore et al., 1985; Schneiderman et al., 1993), a fracture line within 7.5 cm of the lunate fossa (Rettig and Raskin, 2001; Tsismenakis and Tornetta, 2016), ulna variance of greater than 2 mm (Takemoto et al., 2014), and ulna styloid fractures (Giannoulis and Sotereanos, 2007; Tsismenakis and Tornetta, 2016).…”
Section: Introductionmentioning
confidence: 99%